Cycloaddition catalyst, preparation method and application thereof, and preparation method of cyclic carbonate
By supporting the ion exchange resin on the molded molecular sieve, an efficient cycloaddition catalyst is formed, which solves the problem of insufficient stability and strength of the existing catalyst, and achieves efficient continuous use and high yield cycloaddition reactions.
Patent Information
- Application Number
- CN202310809621.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-04
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2043-07-04
AI Technical Summary
The existing cycloaddition catalysts are insufficient in stability and strength during recycling, resulting in a decrease in catalytic activity and it is difficult to meet the needs of industrial production.
A molded molecular sieve is used as a support to support the ion exchange resin, and an efficient cycloaddition catalyst is formed through copolymerization reaction, halomethylation, imidazation and ion exchange, forming a tight interpenetrating structure to improve catalytic activity and stability.
The efficient continuous use of the catalyst is achieved, high catalytic activity and stability are maintained, and the high yield of the cycloaddition product and the effect of multiple cycles is ensured.
Smart Images

Figure CN119281393A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalysts, and in particular to a cycloaddition catalyst and a preparation method and application thereof, and a preparation method of a cyclic carbonate. Background Art
[0002] The new energy industry is an emerging industry that the country focuses on developing. At the same time, the development of new energy vehicles has made the application of power batteries more and more important. As an important component of power batteries, the demand for electrolytes, such as ethylene carbonate and propylene carbonate, has also increased year by year. In addition, alkylene carbonates also have important uses in printing, polymer manufacturing, textiles and other industries.
[0003] The mainstream method for industrial production of alkylene carbonate is to use alkylene oxide and carbon dioxide to react. This method can make full use of carbon dioxide and alleviate the problem of greenhouse gas emissions. The catalyst used in the process is a homogeneous catalytic system. The homogeneous system requires high-concentration catalyst separation, product decomposition caused by catalyst residues, and high costs for the final solid and liquid waste treatment. Therefore, higher requirements are placed on the greenness and economy of the production process of alkylene carbonate.
[0004] Compared with homogeneous catalytic systems, heterogeneous catalytic systems do not have the problems of catalyst product separation and catalyst residue. The heterogeneous catalytic systems currently under development include oxides, MOFs, carbon materials, ionic liquids, etc. 2 O 3 Metal compounds, bifunctional porous metal organic framework material UiO-67-IL, imidazole ionic liquid catalysts supported on chitosan, hydroxyimidazole ionic liquid supported on ion exchange resin, zinc halide catalysts supported on ion exchange resin, etc. Among them, the catalysts supported on ion exchange resin are more studied.
[0005] Zhang et al. reported a hydroxyimidazole ionic liquid PS-HEIMBR supported by an ion exchange resin (Catalysis Today 2009, 148, 361–367). When the catalyst is applied to the epoxy compound / CO2 system, the particle size of the catalyst particles is very high. When the catalyst particles are 100 μm, the conversion rate of propylene oxide and the selectivity of propylene carbonate can reach 99% after 4 hours of reaction at 120°C and 2.5 MPa, which has a high catalytic efficiency. However, 1 mm catalyst particles that have not been ground can only convert 87% of propylene oxide under the same conditions. In addition, bromoethanol is required in the preparation of the catalyst, which increases the production cost of the catalyst and is not conducive to industrial application.
[0006] CN105503608A discloses a halogen-type composite hydroxyimidazole resin catalyst, in which nanomaterials such as carbon nanotubes and hydroxy halides are added during the preparation of the catalyst to improve the material performance. After ethylene oxide is treated at 120°C and 2.0MPa for 3 hours under the action of the catalyst, the conversion rate of ethylene oxide can reach 98.6%, and the selectivity of ethylene carbonate can reach 99.7%. However, the nanomaterials, hydroxy halides and other reagents used in the preparation also increase the production cost of the catalyst, and the reproducibility of the catalyst is not good, and the performance will decrease after 5 repeated uses.
[0007] Xia et al. reported in Appl. Catal. A 2005, 279: 125-129 a system with chitosan loaded with zinc halide as the main catalyst and 1-butyl-3-methylimidazolium bromide as the co-catalyst. At 110°C and 1.5 MPa, propylene oxide and CO 2 After one hour of reaction, the selectivity of propylene carbonate can reach more than 99% and the yield can reach 95%. After adjusting the process parameters, the maximum yield of propylene carbonate can reach 97%. However, due to the insufficient stability and strength of the catalytic system, after repeated use for 5 times, the yield of propylene carbonate decreased from 95% to 87%, which is not conducive to industrial scale-up production.
[0008] DW Park et al. reported a 1-butyl-3-(3-triethoxysilyl)propyl-imidazolium iodide catalyst system supported on carboxymethyl cellulose in Green Chem., 2012, 14, 2933-2940. At 110°C and 1.8 MPa, propylene oxide and CO 2 After 2 hours of reaction, the selectivity of propylene carbonate can reach more than 99%, and the yield can reach 98.6%, which has a high catalytic rate. The catalyst system also has the problems of low catalyst strength and insufficient stability. After repeated use for 4 times, the yield of the product is reduced from 98% to 71%.
[0009] LN He reported in Green Chem., 2005, 7, 518–523 that the selectivity of propylene carbonate and CO2 could reach 99.8% and the yield could reach 99.2% under the catalysis of conventional ion exchange resin D201 at 100 degrees and 8 MPa for 24 hours, showing extremely high activity. After repeated use for 5 times, the selectivity of propylene carbonate did not show a significant decrease, but the yield had dropped to 94%.
[0010] It can be seen that although heterogeneous catalytic systems, including ion exchange resin catalysts, have many advantages, there are still some shortcomings. Research and development of a highly stable and strong heterogeneous catalytic system is still a hot topic in the research of epoxide / carbon dioxide addition catalysts. Summary of the invention
[0011] The purpose of the present invention is to overcome the problem of poor recyclability of existing cycloaddition catalysts, and to provide a cycloaddition catalyst and a preparation method and application thereof, and a preparation method of cyclic carbonate. The cycloaddition catalyst has excellent catalytic activity, and the catalyst can be used continuously for multiple times.
[0012] In order to achieve the above object, the first aspect of the present invention provides a cycloaddition catalyst, wherein the catalyst comprises a carrier formed of a shaped molecular sieve and an ion exchange resin loaded on the carrier, and the catalyst has a structure as shown in the following formula (1):
[0013]
[0014] In formula (1), As a carrier, is a styrene copolymer segment, R 1 is an alkyl or aryl group, X - It is an anion.
[0015] The second aspect of the present invention provides a method for preparing the catalyst described in the first aspect of the present invention, wherein the preparation method comprises: (1) subjecting a carrier adsorbed with an oil phase to a copolymerization reaction; (2) subjecting the molecular sieve / resin spheres obtained by the copolymerization reaction to halogenation, imidazole treatment, and ion exchange; wherein the oil phase contains a styrene copolymer monomer, a crosslinking agent, and an initiator.
[0016] The third aspect of the present invention provides use of the cycloaddition catalyst described in the first aspect of the present invention in the preparation of cyclic carbonates.
[0017] The fourth aspect of the present invention provides a method for preparing a cyclic carbonate, wherein the preparation method comprises: in the presence of the cycloaddition catalyst described in the first aspect of the present invention, an epoxy compound and carbon dioxide undergo a cycloaddition reaction.
[0018] Through the above technical scheme, the cycloaddition catalyst of the present invention is a heterogeneous catalyst, which has high strength, is easy to separate after use, has high catalytic activity, and has high stability. The catalyst can be used continuously for multiple times. For example, using it as a cycloaddition catalyst can obtain a high yield of cycloaddition products, and after the catalyst is recycled for multiple times, a high yield of cycloaddition products can be obtained. DETAILED DESCRIPTION
[0019] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0020] In the present invention, the term "alkyl" may be a branched alkyl or a straight-chain alkyl, and the present invention has no particular limitation.
[0021] In the present invention, "room temperature" refers to 15-30°C.
[0022] In the present invention, the method of "drying / drying" is a conventional method in the art, and the drying can be done under normal pressure or in a vacuum environment, for example, at 80-110°C for 8-20 hours, or at 50-70°C for 10-15 hours under vacuum. The present invention has no particular limitation on this, and those skilled in the art can make a selection according to their needs.
[0023] The first aspect of the present invention provides a cycloaddition catalyst, wherein the catalyst comprises a carrier formed of a shaped molecular sieve and an ion exchange resin loaded on the carrier, and the catalyst has a structure as shown in the following formula (1):
[0024]
[0025] In formula (1), As a carrier, is a styrene copolymer segment, R 1 is an alkyl or aryl group, X - It is an anion.
[0026] In the present invention, it is understood that The structure is an ion exchange resin, and the catalyst includes an ion exchange resin loaded on a carrier. The cycloaddition catalyst in the present invention belongs to a heterogeneous catalyst, which not only has excellent catalytic performance when used, but also can be used continuously for multiple times. The inventors have studied and analyzed that the molded molecular sieve has a molecular sieve pore and a molded pore, and the ion exchange resin forms an interpenetrating structure with the molded molecular sieve, which can better improve the network density of the interpenetrating structure, so that the catalytic active sites of the catalyst can better and stably play a catalytic role, and the ion exchange resin can be more stably loaded on the carrier to play a catalytic role.
[0027] According to the present invention, it can be understood that the styrene copolymer segment is a structural unit containing a styrene comonomer, and in some embodiments, the styrene copolymer segment contains a structural unit a from a styrene comonomer and a structural unit b from a crosslinking agent. Using the above embodiment, the catalyst has good catalytic activity and stability.
[0028] According to the present invention, as long as the purpose of the present invention can be achieved, the content of the structural unit a and the structural unit b is not particularly limited. In some embodiments, based on the total mass of the structural unit a and the structural unit b, the content of the structural unit a is 80-98% by mass, and the content of the structural unit b is 2-20% by mass. Using the above embodiment, the catalyst has good catalytic activity and stability.
[0029] According to the present invention, as long as the purpose of the present invention can be achieved, the specific type of the styrene comonomer providing the structural unit a is not particularly limited. In some embodiments, the structure of the styrene comonomer is as shown in formula (2):
[0030]
[0031] In formula (2), R 11 is alkyl or hydrogen, R 12 is alkyl or hydrogen.
[0032] According to the present invention, in some preferred embodiments, in formula (2), R 11 C 1 -C 6 Alkyl or hydrogen. With the above-mentioned implementation, the catalyst has better catalytic performance and stability.
[0033] According to the present invention, in some preferred embodiments, in formula (2), R 12 C 1 -C 4 Alkyl or hydrogen. With the above-mentioned implementation, the catalyst has better catalytic performance and stability.
[0034] According to the present invention, it can be understood by those skilled in the art that the segments in the ion exchange segments are skeleton structures formed by copolymerization of styrene-based comonomers and crosslinking agents. As long as the purpose of the present invention can be achieved, the selection of the crosslinking agent is not limited. Any crosslinking agent containing two or more double bonds and capable of being initiated by styrene-based free radicals can be used as the crosslinking agent of the present invention. In some preferred embodiments, the crosslinking agent is selected from one or more of ethylene glycol dimethacrylate, dipropylene glycol, 1,1-(4-vinylphenyl)methane and divinylbenzene.
[0035] According to the present invention, in some preferred embodiments, in formula (1), R1 C 1 -C 6 Alkyl, such as methyl, ethyl, propyl, butyl, pentyl, hexyl, preferably C 1 -C 4 By adopting the above-mentioned embodiment, the catalyst has good catalytic activity and stability.
[0036] According to the present invention, in some embodiments, in formula (1), X - It is a halogen ion (such as chloride ion, bromide ion, iodide ion, etc.) and / or an organic acid anion (such as acetate ion, formate ion, hydrogen oxalate ion, etc.) By adopting the above embodiment, the catalyst has good catalytic activity and stability.
[0037] According to the present invention, in some preferred embodiments, in formula (1), X - The ions are one or more of chloride ions, bromide ions, iodide ions and formate ions. By adopting the above-mentioned embodiment, the catalyst has good catalytic activity and stability.
[0038] According to the present invention, it can be understood that when X - It can be in a single ion form, such as all chloride ions, which can be obtained by complete ion exchange, X - It can also be two or more different ions. In this case, it can be obtained by partial ion exchange, so that the anion is in two or more forms, such as in Cl - If less than the theoretical amount of bromide ions is added to the catalyst, the final anion form is Cl - With B r- Based on the convenience of preparation, the embodiments of the present invention are all in the form of X - The advantages of the present invention are illustrated by using a single ion form, but the present invention is not limited thereto.
[0039] According to the present invention, as long as the purpose of the present invention can be achieved, there is no particular limitation on the loading amount of the ion exchange resin on the carrier. In some embodiments, the loading amount of the ion exchange resin is 10-55wt%, preferably 15-45wt%. With the above-mentioned embodiment, the ion exchange resin and the carrier can better cooperate with each other, and the catalyst has excellent catalytic activity and stability.
[0040] According to the present invention, in some embodiments, the specific surface area of the catalyst is 30-500m 2 / g, preferably 50-200m 2 By adopting the above-mentioned embodiment, the catalyst has excellent active sites and can maintain excellent catalytic activity during multiple cycles of use.
[0041] According to the present invention, it can be understood that the molded molecular sieve is made of molecular sieve (i.e. molecular sieve raw powder) and optionally a molding aid through a molding device, and optionally a product formed after exchange at high temperature. As long as the purpose of the present invention can be achieved, the shape of the molded molecular sieve is not particularly limited. In some embodiments, the shape of the molded molecular sieve is selected from one or more of strips, spheres and columns. Using the above-mentioned embodiment, the ion exchange resin can form a closer structure with the catalyst, and the catalytic activity and stability of the catalyst are better.
[0042] According to the present invention, as long as the purpose of the present invention can be achieved, the particle size of the shaped molecular sieve is not particularly limited. In some embodiments, the particle size of the shaped molecular sieve is 0.4-5 mm, preferably 1.3-2.4 mm. Using the above embodiment, the catalyst has better catalytic activity.
[0043] According to the present invention, in some embodiments, the specific surface area of the shaped molecular sieve is 300-1000m 2 / g, preferably 400-700m 2 By adopting the above-mentioned implementation mode, the catalyst has better catalytic activity and stability.
[0044] According to the present invention, in some embodiments, the compressive strength of the shaped molecular sieve is greater than or equal to 30 N. With the aforementioned embodiment, the catalyst has better catalytic activity and stability.
[0045] According to the present invention, in some embodiments, the molecular sieve in the shaped molecular sieve comprises an aluminosilicate molecular sieve. Using the above embodiments, the catalyst has excellent catalytic activity and stability.
[0046] According to the present invention, in some embodiments, the aluminosilicate molecular sieve is selected from one or more of A-type molecular sieve, zeolite-type molecular sieve, X-type molecular sieve, ZSM-type molecular sieve and Y-type molecular sieve. Using the above embodiments, the catalyst has excellent catalytic activity and stability.
[0047] According to the present invention, in some preferred embodiments, the aluminosilicate molecular sieve is a type A molecular sieve. With the above embodiments, the catalyst has excellent catalytic activity and stability.
[0048] According to the present invention, in some more preferred embodiments, the A-type molecular sieve is selected from one or more of 3A-type molecular sieve, 4A-type molecular sieve and 5A-type molecular sieve. Using the above embodiments, the catalyst has excellent catalytic activity and stability.
[0049] The second aspect of the present invention provides a method for preparing the catalyst described in the first aspect of the present invention, wherein the preparation method comprises: (1) subjecting a carrier adsorbed with an oil phase to a copolymerization reaction; (2) subjecting the molecular sieve / resin spheres obtained by the copolymerization reaction to halogenation, imidazole treatment, and ion exchange; wherein the oil phase contains a styrene copolymer monomer, a crosslinking agent, and an initiator.
[0050] In the present invention, the molded molecular sieve carrier in the present application has pores, and all or most of the styrene copolymer monomers, cross-linking agents and initiators are adsorbed in the pores of the carrier, and then copolymerization reaction is carried out to form styrene copolymer segments to obtain molecular sieve / resin balls, and then the molecular sieve / resin balls are subjected to a series of functionalization treatments to form a catalyst including an ion exchange resin loaded on the carrier. The ion exchange resin and the carrier (molded molecular sieve) can form a tight and stable interpenetrating structure and have more catalytic active sites. The prepared catalyst has excellent catalytic activity and can be recycled many times.
[0051] According to the present invention, a suitable amount of adsorption of the oil phase can be selected according to the loading amount of the ion exchange resin. It takes a certain amount of time for the oil phase to be adsorbed on the carrier. As long as the purpose of the present invention can be achieved, the manner in which the oil phase is adsorbed on the carrier is not particularly limited. In some embodiments, the method for obtaining the carrier adsorbed with the oil phase includes: immersing the carrier in the oil phase, and then filtering to obtain the carrier adsorbed with the oil phase.
[0052] According to the present invention, in some preferred embodiments, based on the total weight of the oil phase and the carrier, the amount of the styrene comonomer is 35-60wt%, the amount of the crosslinking agent is 2-10wt%, the amount of the initiator is 0.1-3wt%, and the amount of the carrier is 30-60wt%. The catalyst prepared by the above embodiment has excellent stability and catalytic activity.
[0053] According to the present invention, as long as the purpose of the present invention can be achieved, the soaking conditions are not particularly limited. In order to allow the oil phase to react after being absorbed by the carrier, in some embodiments, the soaking conditions include: room temperature.
[0054] According to the present invention, in some embodiments, the soaking conditions include: the soaking time is 6-36 hours.
[0055] According to the present invention, in some preferred embodiments, in step (1), the conditions of the copolymerization reaction include: the reaction temperature is 80-100°C.
[0056] According to the present invention, in some preferred embodiments, in step (1), the conditions of the copolymerization reaction include: the reaction time is 4-12 hours.
[0057] According to the present invention, it can be understood that the product of the copolymerization reaction is molecular sieve / resin balls, but there may be some residual monomer raw materials in the product. In order to obtain relatively pure molecular sieve / resin balls, those skilled in the art can choose a suitable post-treatment method, such as drying after washing, specifically, using methanol for elution during washing.
[0058] According to the present invention, those skilled in the art can select a halomethylation method according to the present invention. In some embodiments, the halomethylation method comprises: in the presence of a Lewis acid catalyst, the molecular sieve / resin ball and the halomethylation agent carry out a halomethylation reaction, followed by a first purification and separation. Using the above embodiment, the prepared catalyst has good catalytic activity.
[0059] According to the present invention, the dosage of Lewis acid catalyst and halomethylation agent can be selected as needed. In some embodiments, the dosage of Lewis acid catalyst is 2-15wt% of the mass of molecular sieve / resin ball; in some embodiments, molecular sieve / resin ball: halomethylation agent = 1g: (1-5)mL.
[0060] According to the present invention, in some embodiments, the Lewis acid catalyst is at least one halide of Zn, Al, Ti, Sb, and Zr, such as ZnCl 2 、AlCl 3 、TiCl 4 , SbF 5 and ZrCl 4 At least one of .
[0061] According to the present invention, in some embodiments, the halomethylating agent is a halomethyl C 1 -C 4 Alkyl ethers such as chloromethyl methyl ether, bromomethyl methyl ether, chloromethyl ethyl ether, bromomethyl ethyl ether, chloromethyl propyl ether, bromomethyl propyl ether, chloromethyl butyl ether and bromomethyl butyl ether and the like.
[0062] According to the present invention, in some embodiments, the conditions of the halomethylation reaction include: the reaction temperature is 50-60°C.
[0063] According to the present invention, in some embodiments, the conditions of the halomethylation reaction include: the reaction time is 5-15 hours.
[0064] According to the present invention, there may be some residual raw materials after the halomethylation reaction. After the halomethylation reaction, a first purification and separation can be performed as needed to obtain the halomethylated product (molecular sieve / resin halide ball). Those skilled in the art can select the first purification and separation method as needed. For example, after the halomethylation reaction, the halogenated mother liquor is filtered out, and then it is repeatedly washed with methanol, and finally dried to obtain the halomethylated product (molecular sieve / resin halide ball).
[0065] According to the present invention, it can be understood that the product after halomethylation is a molecular sieve / resin halide ball. In order to ensure the smooth progress of the subsequent imidazole reaction, the imidazole reaction is carried out in the presence of a solvent as needed. In some embodiments, the imidazole reaction method includes: in the presence of a solvent, the product after halomethylation is subjected to an imidazole reaction with an imidazole compound shown in formula (3), followed by a second purification and separation.
[0066]
[0067] In formula (3), R 1 The definition of is the same as that of formula (1).
[0068] According to the present invention, in some embodiments, the conditions for the imidazole reaction include: reacting under reflux.
[0069] According to the present invention, in some embodiments, the conditions of the imidazole reaction include: the reaction time is 10-30 hours.
[0070] According to the present invention, there may be some residual raw materials after the imidazole reaction is completed. The imidazole reaction needs to be subjected to a second purification and separation to obtain the imidazole product (molecular sieve / resin imidazole balls). Those skilled in the art can select the second purification and separation method as needed. For example, after the imidazole reaction, the reaction solution is filtered to remove the reaction solution, and then washed with ethyl acetate, 0.05-0.15 mol / L HCl, and water in sequence, and finally dried to obtain the imidazole product (molecular sieve / resin imidazole balls).
[0071] According to the present invention, in some embodiments, the ion exchange method comprises: the imidazole product (molecular sieve / resin imidazole ball) is reacted with an anion X - An alkali metal salt aqueous solution is subjected to an ion exchange reaction, and then washed to neutrality and dried, wherein X - The same as the definition in formula (1); specifically, when performing ion exchange, the molecular sieve / resin imidazole balls can be loaded into the exchange column, and then the anion is X - The anion is X -The amount of the alkali metal salt solution is not particularly limited, and the exchange can be saturated. For example, the molecular sieve / resin imidazole ball anion is X - The volume ratio of the alkali metal salt aqueous solution is 1:(8-30).
[0072] According to the present invention, in some embodiments, the solubility of the alkali metal salt aqueous solution is 0.1-1 mol / L.
[0073] According to the present invention, the anions that can be mentioned are X - Alkali metal salts include NaX, KX, FeX 3 , CaX 2 wait.
[0074] The third aspect of the present invention provides use of the cycloaddition catalyst described in the first aspect of the present invention in the preparation of cyclic carbonates.
[0075] In the present invention, when the cycloaddition catalyst of the present invention is used to prepare cyclic carbonate, not only a high yield of cyclic carbonate product can be obtained, but also the cycloaddition catalyst can be repeatedly used to obtain cyclic carbonate product.
[0076] The fourth aspect of the present invention provides a method for preparing a cyclic carbonate, wherein the preparation method comprises: in the presence of the cycloaddition catalyst described in the first aspect of the present invention, an epoxy compound and carbon dioxide undergo a cycloaddition reaction.
[0077] In the present invention, in the presence of the specific cycloaddition catalyst of the present invention, the epoxy compound and carbon dioxide can better carry out the cycloaddition reaction to obtain the cyclic carbonate with high yield, and the cycloaddition catalyst can also be repeatedly used to carry out the cycloaddition reaction to obtain the cyclic carbonate with high yield.
[0078] According to the present invention, the corresponding epoxy compound can be selected as a raw material according to the type of the desired cyclic carbonate. In some embodiments, the structure of the epoxy compound is as shown in formula (I):
[0079]
[0080] In formula (I), R is hydrogen, alkyl or phenyl.
[0081] According to the present invention, in some preferred embodiments, in formula (I), R is hydrogen, C 1 -C 3 Alkyl or phenyl.
[0082] According to the present invention, the epoxy compound may be exemplified by ethylene oxide, propylene oxide, butylene oxide or styrene oxide.
[0083] According to the present invention, in some embodiments, the conditions of the cycloaddition reaction include: the mass ratio of the cycloaddition catalyst to the epoxy compound is (0.001-1):1, preferably (0.1-0.3):1.
[0084] According to the present invention, in some embodiments, the conditions of the cycloaddition reaction include: the reaction temperature is 60-180°C, preferably 100-160°C.
[0085] According to the present invention, in some embodiments, the conditions of the cycloaddition reaction include: the reaction pressure is 0.1-10 MPa, preferably 2-5 MPa.
[0086] According to the present invention, in some embodiments, the conditions of the cycloaddition reaction include: the reaction time is 1-12h.
[0087] The present invention will be described in detail below by way of examples. In the following examples and comparative examples:
[0088] The prepared cycloaddition catalysts were used in the cycloaddition reaction of propylene oxide and carbon dioxide, respectively, and the experiment was as follows:
[0089] Under the protection of high-purity nitrogen, 40.0 g of propylene oxide and 5 g of cycloaddition catalyst were added to a 200 mL autoclave and filled with 1.0 MPa CO 2 , heat up to 120℃, and then fill with CO 2 The reaction pressure was maintained at 3.0 MPa. After reacting for 4 hours, the catalyst was removed by filtration and tested.
[0090] Example 1
[0091] In a 500 ml flask, add 150 g of styrene, 12 g of divinylbenzene, and 3 g of benzoyl peroxide. After stirring for 60 minutes, add 100 g of spherical 5A molecular sieve (particle size 2.2 mm, specific surface area 390 m 2 / g, compressive strength of 65N), soaked for 24 hours; then filtered the oil phase to obtain a molecular sieve adsorbed with the oil phase, placed it at 90 ° C for 10 hours, then rinsed with methanol and dried to obtain a molecular sieve / resin ball;
[0092] In a 500mL three-necked flask, add 60g of molecular sieve / resin balls and 200mL of chloromethyl ether, let stand at room temperature for 2 hours, then add 8g of zinc chloride as a catalyst and start stirring, gradually heat to 60°C and react for 10 hours, cool to room temperature after chloromethylation, filter out the chlorinated mother liquor, wash with methanol, and dry at 100°C for 8 hours to obtain molecular sieve / resin chlorine balls;
[0093] In a 500 mL three-necked flask, add 60 g of molecular sieve / resin chloride balls, 130 ml of N-methylimidazole, and 200 ml of N,N-dimethylformamide, react under reflux for 24 hours, then cool to room temperature, filter out the reaction solution, wash with ethyl acetate, 0.1 mol / L HCl, and deionized water in sequence, and then bake at 80°C for 16 hours to obtain molecular sieve / resin imidazole balls;
[0094] In the exchange column, 50 ml of molecular sieve / resin imidazole balls were added and exchanged with 500 mL of 0.5 mol / L NaBr deionized water solution; then washed with deionized water until the washing liquid was neutral, and vacuum dried to obtain a cycloaddition catalyst, which was recorded as Cat-A1.
[0095] The structure of the cycloaddition catalyst is:
[0096] It is a spherical 5A type molecular sieve. It is a styrene copolymer matrix;
[0097] Specific surface area: 58m 2 / g;
[0098] The loading amount of the ion exchange resin was 20 wt%.
[0099] The cycloaddition catalyst was used to carry out the initial cycloaddition reaction with carbon dioxide, and the experimental results are shown in Table 1;
[0100] The catalyst after the cycloaddition reaction was filtered, and then propylene oxide and dioxygen were used according to the cycloaddition reaction to obtain the cycloaddition catalyst, which was recycled twice. Similarly, the catalytic carbon ring addition reaction was carried out for 5 cycles (the cycloaddition catalysts for each cycle were recorded as Cat-A1, Cat-A1-2, Cat-A1-3, Cat-A1-4, and Cat-A1-5, respectively). The experimental results are shown in Table 1.
[0101] Example 2
[0102] In a 500 ml flask, add 150 g of styrene, 18 g of divinylbenzene, and 4 g of benzoyl peroxide. After stirring for 1 hour, add 100 g of columnar 3A molecular sieve (particle size 1.5 mm; specific surface area 500 m 2 / g; compressive strength is 80N), soaked at room temperature for 15 hours, then filtered the oil phase to obtain a molecular sieve adsorbed with the oil phase, placed at 90 ° C for 10 hours, then rinsed with methanol and dried to obtain a molecular sieve / resin;
[0103] In a 500mL three-necked flask, add 100g of molecular sieve / resin and 300mL of chloromethyl ether, let stand at room temperature for 2 hours, then add 8g of zinc chloride as a catalyst and start stirring, gradually heat to 60°C and react for 12 hours, cool to room temperature after the reaction, filter out the chlorinated mother liquor, wash with methanol, and dry at 100°C for 8 hours to obtain a molecular sieve / chlororesin;
[0104] Add 90 g molecular sieve / resin chloride balls, 200 ml N-methylimidazole and 200 ml N,N-dimethylformamide into a 500 mL three-necked flask, react for 24 hours under reflux and then cool to room temperature, filter out the reaction solution, wash with ethyl acetate, 0.1 mol / L HCl and deionized water in sequence, and then bake at 80°C for 16 hours to obtain molecular sieve / resin imidazole balls;
[0105] In the exchange column, 100 ml of molecular sieve / resin imidazole balls were added and exchanged with 2000 mL of 0.25 mol / L NaBr deionized water solution; then washed with deionized water until the washing liquid was neutral, and vacuum dried to obtain a cycloaddition catalyst, which was recorded as Cat-A2.
[0106] The structure of the cycloaddition catalyst is:
[0107] It is a columnar 3A type molecular sieve. It is a styrene copolymer matrix;
[0108] Specific surface area: 150m 2 / g
[0109] The loading amount of the ion exchange resin was 30 wt%.
[0110] The cycloaddition reaction of propylene oxide and carbon dioxide was carried out using a cycloaddition catalyst. The experimental results are shown in Table 1.
[0111] Example 3
[0112] In a 500 ml flask, add 150 g of styrene, 6 g of dipropylene phenyl, and 5 g of benzoyl peroxide. After stirring for 1 hour, add 100 g of spherical 4A molecular sieve (particle size 3.2 mm; specific surface area 900 m 2 / g; compressive strength is 85N), soaked at room temperature for 6 hours, then filtered the oil phase to obtain a molecular sieve adsorbed with the oil phase, placed at 90 ° C for 10 hours, then rinsed with methanol and dried to obtain a molecular sieve / resin;
[0113] In a 500mL three-necked flask, add 100g of molecular sieve / resin and 300mL of chloromethyl ether, let stand at room temperature for 2 hours, then add 3g of zinc chloride as a catalyst and start stirring, gradually heat to 50°C and react for 12 hours, cool to room temperature after the reaction, filter out the chlorinated mother liquor, wash repeatedly with methanol, and dry at 100°C for 8 hours to obtain a molecular sieve / chlororesin;
[0114] Add 90 g molecular sieve / resin chloride balls, 150 ml N-methylimidazole and 200 ml N,N-dimethylformamide into a 500 mL three-necked flask, react for 24 hours under reflux and then cool to room temperature, then filter out the reaction solution, wash with ethyl acetate, 0.1 mol / L HCl and deionized water in sequence, and then dry under vacuum at 50°C for 10 hours to obtain molecular sieve / resin imidazole balls;
[0115] In the exchange column, 100 ml of molecular sieve / resin imidazole balls were added and exchanged with 2000 mL of 0.25 mol / L NaBr deionized water solution; then washed with deionized water until the washing liquid was neutral, and vacuum dried to obtain a cycloaddition catalyst, which was recorded as Cat-A3.
[0116] The structure of the cycloaddition catalyst is:
[0117] It is a spherical 4A type molecular sieve. It is a styrene copolymer matrix;
[0118] Specific surface area: 253m 2 / g;
[0119] The loading amount of the ion exchange resin was 17 wt%.
[0120] The cycloaddition reaction of propylene oxide and carbon dioxide was carried out using a cycloaddition catalyst. The experimental results are shown in Table 1.
[0121] Example 4
[0122] The method according to Example 1 is different in that:
[0123] The imidazole reagent used was N-propylimidazole instead of N-methylimidazole, and the other conditions were the same. The final cycloaddition catalyst was recorded as Cat-A4.
[0124] The structure of the cycloaddition catalyst is:
[0125] It is a spherical 5A type molecular sieve. It is a styrene copolymer matrix;
[0126] Specific surface area: 53m2 / g
[0127] The loading amount of the ion exchange resin was 25 wt%.
[0128] The cycloaddition reaction of propylene oxide and carbon dioxide was carried out using a cycloaddition catalyst. The experimental results are shown in Table 1.
[0129] Example 5
[0130] The method of Example 2 was followed, except that α-methylstyrene was used instead of styrene, and ethylene glycol dimethacrylate was used instead of divinylbenzene. Other conditions were the same, and the cycloaddition catalyst finally obtained was recorded as Cat-A5.
[0131] The structure of the cycloaddition catalyst is:
[0132] It is a columnar 3A type molecular sieve. It is a styrene copolymer matrix;
[0133] Specific surface area: 140m 2 / g
[0134] The loading amount of the ion exchange resin was 34 wt%.
[0135] The cycloaddition reaction of propylene oxide and carbon dioxide was carried out using a cycloaddition catalyst. The experimental results are shown in Table 1.
[0136] Example 6
[0137] The method of Example 3 was followed, except that phenylimidazole was used instead of methylimidazole. The other conditions were the same, and the cycloaddition catalyst finally obtained was recorded as Cat-A6.
[0138] The structure of the cycloaddition catalyst is:
[0139] It is a spherical 4A type molecular sieve. It is a styrene copolymer matrix;
[0140] Specific surface area: 185m 2 / g
[0141] The loading amount of the ion exchange resin was 30 wt%.
[0142] The cycloaddition reaction of propylene oxide and carbon dioxide was carried out using a cycloaddition catalyst. The experimental results are shown in Table 1.
[0143] Example 7
[0144] The method of Example 1 is followed except that a spherical ZSM-5 molecular sieve (particle size 2-3 mm; specific surface area 360 m 2 / g; compressive strength is 70) to replace the spherical 5A molecular sieve, and the other conditions are the same. The final cycloaddition catalyst is recorded as Cat-A7.
[0145] The structure of the cycloaddition catalyst is:
[0146] It is a spherical ZSM-5 molecular sieve. It is a styrene copolymer matrix;
[0147] Specific surface area: 63m 2 / g;
[0148] The loading amount of the ion exchange resin was 18 wt%.
[0149] Comparative Example 1
[0150] According to the method of Example 1, except that the formed molecular sieve is replaced by a powdered molecular sieve, and the other conditions are the same, a catalyst intermediate is prepared;
[0151] The catalyst intermediate was rolled into a hydrated catalyst with a diameter of 2 mm, which was named Cat-B1.
[0152] The final catalyst was designated as Cat-B1.
[0153] The specific surface area of the cycloaddition catalyst is: 45m 2 / g;
[0154] The loading amount of the ion exchange resin was 16 wt%.
[0155] The cycloaddition catalyst was used to carry out the initial cycloaddition reaction with carbon dioxide. The experimental results are shown in Table 1.
[0156] Table 1
[0157]
[0158] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A cycloaddition catalyst, characterized in that The catalyst comprises a carrier formed of a shaped molecular sieve and an ion exchange resin loaded on the carrier, and the catalyst has a structure as shown in the following formula (1): For the vector, is a styrene copolymer segment, R1 is an alkyl or aryl group, X - It is an anion.
2. The catalyst according to claim 1, wherein The styrene copolymer segment contains a structural unit a derived from a styrene copolymer monomer and a structural unit b derived from a cross-linking agent; Preferably, based on the total mass of the structural unit a and the structural unit b, the content of the structural unit a is 80-98 mass %, and the content of the structural unit b is 2-20 mass %; and / or The structure of the styrene comonomer is shown in formula (2): In formula (2), R 11 is alkyl or hydrogen, R 12 is alkyl or hydrogen, preferably R 11 is C1-C6 alkyl or hydrogen and / or R 12 is C1-C4 alkyl or hydrogen; The crosslinking agent is selected from a crosslinking agent containing two or more double bonds and capable of initiating with styrene free radicals, preferably one or more of ethylene glycol dimethacrylate, dipropylene benzene, 1,1-(4-vinylphenyl)methane and divinyl benzene.
3. The catalyst according to claim 1 or 2, wherein In formula (1), R1 is a C1-C6 alkyl group, preferably a C1-C4 alkyl group; and / or In formula (1), X - is a halogen ion and / or an organic acid anion, preferably one or more of a chloride ion, a bromide ion, an iodide ion and a formate ion; and / or The loading amount of the ion exchange resin is 10-55wt%, preferably 15-45wt%; and / or The specific surface area of the catalyst is 30-500m 2 / g, preferably 50-200m 2 / g.
4. The catalyst according to any one of claims 1 to 3, wherein The shape of the shaped molecular sieve is selected from one or more of strip, spherical and columnar; and / or The particle size of the shaped molecular sieve is 0.4-5 mm, preferably 1.3-2.4 mm; and / or The specific surface area of the shaped molecular sieve is 300-1000m 2 / g, preferably 400-700m 2 / g; and / or The compressive strength of the shaped molecular sieve is greater than or equal to 30N; and / or The molecular sieve in the molded molecular sieve includes aluminosilicate molecular sieve; Preferably, the aluminosilicate molecular sieve is selected from one or more of type A molecular sieve, zeolite molecular sieve, type X molecular sieve, ZSM molecular sieve and type Y molecular sieve, preferably type A molecular sieve; Preferably, the A-type molecular sieve is one or more selected from the group consisting of 3A-type molecular sieve, 4A-type molecular sieve and 5A-type molecular sieve.
5. A method for preparing the catalyst according to any one of claims 1 to 4, characterized in that: The preparation method comprises: (1) The carrier adsorbed with the oil phase undergoes copolymerization reaction; (2) the molecular sieve / resin spheres obtained by the copolymerization reaction are subjected to halomethylation, imidazoleization, and ion exchange; Wherein, the oil phase contains styrene comonomer, crosslinking agent and initiator.
6. The preparation method according to claim 5, wherein: The method for obtaining the carrier adsorbed with the oil phase comprises: soaking the carrier in the oil phase, and then filtering to obtain the carrier adsorbed with the oil phase; Preferably, based on the total mass of the oil phase and the carrier, the amount of the styrene comonomer is 35-60wt%, the amount of the crosslinking agent is 2-10wt%, the amount of the initiator is 0.1-3wt%, and the amount of the carrier is 30-60wt%; and / or The soaking conditions include: room temperature and / or soaking time of 6-36 hours; and / or In step (1), the conditions of the copolymerization reaction include: a reaction temperature of 80-100° C.; and / or a reaction time of 4-12 hours.
7. The preparation method according to claim 5 or 6, wherein: The halomethylation method comprises: in the presence of a Lewis acid catalyst, the molecular sieve / resin ball and the halomethylation agent carry out a halomethylation reaction, followed by a first purification and separation, preferably the conditions of the halomethylation reaction include: a reaction temperature of 50-60° C. and / or a reaction time of 5-15 hours; and / or The imidazole method comprises: in the presence of a solvent, the product after halogenation is subjected to an imidazole reaction with an imidazole compound represented by formula (3), followed by a second purification and separation. Preferably, the imidazole reaction conditions include: reacting under reflux and / or the reaction time is 10-30 hours, In formula (3), R1 is defined the same as in formula (1); and / or The ion exchange method comprises: the product after imidazole is reacted with an anion X - An alkali metal salt aqueous solution is subjected to ion exchange reaction, and then washed to neutrality and dried; wherein X - Same as the definition in formula (1).
8. Use of the cycloaddition catalyst according to any one of claims 1 to 4 in the preparation of cyclic carbonates.
9. A method for preparing a cyclic carbonate, characterized in that: The preparation method comprises: in the presence of the cycloaddition catalyst described in any one of claims 1 to 4, an epoxide compound and carbon dioxide undergo a cycloaddition reaction; Preferably, the structure of the epoxy compound is as shown in formula (I): In formula (I), R is hydrogen, alkyl or phenyl, preferably hydrogen, C1-C3 alkyl or phenyl.
10. The preparation method according to claim 9, wherein: The conditions of the cycloaddition reaction include: The mass ratio of the cycloaddition catalyst to the epoxy compound is (0.001-1):1, preferably (0.1-0.3):1; and / or The reaction temperature is 60-180°C, preferably 100-160°C; and / or The reaction pressure is 0.1-10 MPa, preferably 2-5 MPa; and / or The reaction time is 1-12h.
Citation Information
Patent Citations
Production method of ethylene carbonate
CN105503608A
Porous hybrid-resin solid acid catalyst and preparation method thereof
CN101961660A
Method for adopting short-mesoporous solid-base molecular sieve for catalyzing synthesis to obtain biodiesel
CN107876105A
Basic monolithic catalyst with regular pore channels, preparation method of catalyst and application of catalyst in MIBK synthesis process
CN108126748A
Epoxyalkane addition reaction catalyst and application thereof
CN112619705A